2013
DOI: 10.1186/1471-2202-14-17
|View full text |Cite
|
Sign up to set email alerts
|

In vitro neuronal network activity in NMDA receptor encephalitis

Abstract: BackgroundAnti-NMDA-encephalitis is caused by antibodies against the N-methyl-D-aspartate receptor (NMDAR) and characterized by a severe encephalopathy with psychosis, epileptic seizures and autonomic disturbances. It predominantly occurs in young women and is associated in 59% with an ovarian teratoma.ResultsWe describe effects of cerebrospinal fluid (CSF) from an anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis patient on in vitro neuronal network activity (ivNNA). In vitro NNA of dissociated primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…Once generated, cortical neurons grown on MEAs allow non-invasive, long-term measurements of the spontaneous activity ( Maeda et al, 1995 ; Morefield et al, 2000 ; Potter and DeMarse, 2001 ; Van Pelt et al, 2004 ; Wagenaar et al, 2005 , 2006a ; Baltz et al, 2010 ; Gramowski et al, 2010 ; Weir et al, 2014 ) and electrical stimulation of the same cells over extended periods of time ( Wagenaar et al, 2006b ; Brewer et al, 2009 ; Bologna et al, 2010 ; Ide et al, 2010 ; Weihberger et al, 2013 ; Keren and Marom, 2014 ). Consequently, such a preparation has a variety of applications as for example studying basic neuronal mechanisms such as information processing, neuronal plasticity, neurotoxicity screening, biocompatibility testing as well as understanding sources of human disorders ( Shahaf and Marom, 2001 ; Eytan et al, 2003 ; Wagenaar et al, 2005 ; Bakkum et al, 2008 ; Kermany et al, 2010 ; Wallach and Marom, 2012 ; Dranias et al, 2013 ; Jantzen et al, 2013 ; Charkhkar et al, 2014 ; Frega et al, 2014 ; Gullo et al, 2014a , b ; Hedrich et al, 2014 ; Mack et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once generated, cortical neurons grown on MEAs allow non-invasive, long-term measurements of the spontaneous activity ( Maeda et al, 1995 ; Morefield et al, 2000 ; Potter and DeMarse, 2001 ; Van Pelt et al, 2004 ; Wagenaar et al, 2005 , 2006a ; Baltz et al, 2010 ; Gramowski et al, 2010 ; Weir et al, 2014 ) and electrical stimulation of the same cells over extended periods of time ( Wagenaar et al, 2006b ; Brewer et al, 2009 ; Bologna et al, 2010 ; Ide et al, 2010 ; Weihberger et al, 2013 ; Keren and Marom, 2014 ). Consequently, such a preparation has a variety of applications as for example studying basic neuronal mechanisms such as information processing, neuronal plasticity, neurotoxicity screening, biocompatibility testing as well as understanding sources of human disorders ( Shahaf and Marom, 2001 ; Eytan et al, 2003 ; Wagenaar et al, 2005 ; Bakkum et al, 2008 ; Kermany et al, 2010 ; Wallach and Marom, 2012 ; Dranias et al, 2013 ; Jantzen et al, 2013 ; Charkhkar et al, 2014 ; Frega et al, 2014 ; Gullo et al, 2014a , b ; Hedrich et al, 2014 ; Mack et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of anti-NMDAR antibodies by immunohistochemistry on rodent brain slices indicates a high hippocampal staining, a moderate cortical staining and a limited cerebellar staining,10 correlating well with the symptomatology. Various studies performed using animal models and in vitro suggest that the antibody decreases the surface expression and total density17,41 of NMDARs, leading to an alteration in synaptic plasticity and synaptic transmission 41,42. These data point toward a direct pathogenic role of antibodies on the NMDAR itself.…”
Section: Anti-nmdar Encephalitismentioning
confidence: 99%
“…A decrease of the NMDAR-mediated current seems to be caused only by internalization of NMDAR and not by an antagonistic effect (Moscato et al, 2014). Acute application of patients' CSF also decreased neuronal network activity in neuronal cultures (Jantzen et al, 2013). Finally, two studies reported an alteration of NMDARmediated plasticity by patients' NMDAR antibodies as they prevented induction of chemical long-term potentiation (LTP) (Mikasova et al, 2012) and electrophysiologically induced LTP in neuronal cell cultures (Zhang et al, 2012).…”
Section: Glutamate-gated Ion Channelmentioning
confidence: 99%